Assessment of dust emission at the limestone open pit "Milojević Brdo" - Stanić Nikola; Gomilanović Miljan; Doderović Aleksandar; Aksić Nemanja (Mining and Metallurgy Engineering Bor, 2022)
The basis of emission assessment at the Open Pit "Milojević Brdo" is to define the dust distribution depending on the wind influence and dust emitters. This paper presents the data for equipment engaged at the open pit. Through an analytical approach, the total emission of dust emitted by the mining equipment and aeolian erosion in the area of the open pit was determined. The results of this analysis represent a prediction of the state of dust impact on the environment during the exploitation process at the open pit.